Different dissolved organic matter sources sustain microbial life in a sandy beach subterranean estuary – an incubation study - Abarike, Grace A.; Brick, Simone; Engelen, Bert; Niggemann, Jutta (Frontiers in Marine Science, 2024)
In subterranean estuaries (STE), fresh and saline groundwater introduce dissolved organic matter (DOM) of different origin. This DOM serves as substrate for microorganisms that thrive in the STE. In high-energy beaches with dynamic porewater advection, microbial communities face frequent changes in groundwater composition, even at several meters depth. It is unknown how DOM from deep STE groundwater (> 5 m depth) is transformed by prevailing microbial communities. To address this question, we performed sediment incubations in flow-through reactors (FTRs) with deep (6 m depth) STE groundwater of low (1.6) and high salinity (29.1). FTR setups were sampled daily for quantification of dissolved organic carbon (DOC), and at start and end (day 13) of the incubation for analysis of DOM composition, microbial cell numbers and community composition. Solid-phase extracted DOM was molecularly characterized via ultrahigh-resolution Fourier-transform ion cyclotron resonance mass spectrometry. Both groundwater types contained mainly reworked DOM. Corroborating its presumed origin, the fresh groundwater had a more terrestrial DOM signature with a higher proportion of aromatic compounds compared to the saline groundwater. Over the course of the incubation, DOC concentrations increased primarily due to leaching of sedimentary organic matter, providing an additional source of DOM. In all setups, the DOM composition changed significantly from start to end, and similarly for fresh and saline groundwater. From the 2700 molecular formulae (MF) detected on day 0, 34-35% were removed during the incubations, demonstrating the potential of deep STE microbial communities to degrade recalcitrant DOM that is supplied with the advective porewater flow. However, a substantial portion of MF (63-64%) was retained in both groundwater types, indicating that a fraction of deep STE-DOM is resistant to removal. Properties of MF that were newly detected on day 13 (26-28%) were indicative of labile DOM. Some of these newly detected MF were also identified in sediment-leachates, suggesting that beach sediments are a source of fresh DOM for the STE microbial communities. It is likely that due to longer groundwater residence time in the STE, continuous leaching and microbial processing shift the molecular composition of released DOM from more labile to more recalcitrant DOM.